Pengembangan Metode Pembelajaran Kewirausahaan Berbasis Proyek Untuk Meningkatkan Karakter Wirausaha Mahasiswa di Politeknik Negeri Malang - Sulasari, Ayu (STIE Malangkucecwara, 2016)
Attitude mentality potential of entrepreneurship, especially among students need to be developed, with the opportunities that exist and to be the strength to make the authorized capital development. Kalipatrick (1918) Developing an individual to be successful can be achieved by projects that can be done by learners. This study was conducted to obtain a model of entrepreneurial learning development based contextual business problems. It applying the proposed business significantly, this model is expected to be a form of community based education (foster active participation of students in education and training) that is capable of forming new entrepreneurs to reduce poverty, especially in ??Malang. The purpose of this research to determine the development of students entrepreneurial learning method through Project Based Learning approach. The observation is made the group, with each group consist of 5-6 students. The results from this study demonstrated the ability of students to solve problems. Through the development of project-based learning method is seen student interest the development of entrepreneurship shown in the character of students through research variables, that is: leadership / leadership skills were quite good; courage to take risk is still very low; a student perseverance who is well; students' ability to focus on the job they should be improved; and the level of discipline a student who has good enough.